Desenvolvimento e validação de métodos analíticos para controle de qualidade de comprimidos de empagliflozina e estudo preliminar de estabilidade - Biscaino, Pauline Trindade (2018)
Diabetes mellitus (DM) is a disease characterized by a heterogeneous group of metabolic disorders, which present hyperglycemia in common. Different classes of oral antidiabetics, such as empagliflozin, belonging to the class of cotransport inhibitors of sodium-glucose 2 (SGLT-2), are available for treatment. The drug was approved for use in 2014 for the treatment of diabetes mellitus type 2 (DM2), and there are no pharmacopoeial monographs for its determination as raw material and/or tablets. Thus, the focus of this work was the development and validation of qualitative and quantitative methods for the quality control of empagliflozin tablets. The chemical reference substance (SQR) was characterized by methods such as ultraviolet (UV) spectrophotometry, infrared (IV) spectrophotometry, differential scanning calorimetry (DSC) and mass spectrometry. For the identification of the empagliflozin in the tablets, qualitative methods were performed: spectrophotometry (UV), thin layer chromatography (CCD) and capillary electrophoresis (CE). For the quantitative analysis of the tablets, a micellar electrokinetic (MEKC) method was developed and validated using silica capillary (40 cm effective length and 50 μm internal diameter), maintained at 28ºC, voltage +28 kV, hydrodynamic injection of 50 mBar for 4 seconds using electrolytic solution composed of 20 mM tris hydroxymethyl amino methane buffer and 100 mM sodium dodecyl sulfate (SDS) (1:1) pH 10, with detection at 225 nm. The validation was performed according to the current guidelines, evaluating the parameters: specificity, linearity, accuracy, precision, and robustness, and all parameters met the requirements. The analytical conditions provided a six-minute analysis, and the method was linear (r=0.9999) in the range of 50-150 μg/mL, accurate (mean recovery=100.60%), precise (RSD intrad-day 0.79% and inter-day 0.85%), specific and robust. By preliminary stability studies, it was verified that the drug degrades slowly under the usual conditions of forced degradation, and degradation in acidic and alkaline media presented first-order kinetics with t90% of 25.4 and 24.7 h, respectively. The cytotoxicity analysis of solutions of the drug and solutions submitted to degradation showed a slight decrease in cell viability for solutions exposed to UVC and alkaline media. The method of dissolution by UV spectrophotometry was developed and validated according to USP 39 (2016), and the following conditions were optimized: 900 mL of 0.025 M phosphate buffer pH 6.86, maintained at 37 ºC ± 0.5 ºC as dissolution medium, apparatus II (blades), with rotational speed 40 rpm and detection at 225 nm.